2016
DOI: 10.1007/s12104-016-9683-x
|View full text |Cite
|
Sign up to set email alerts
|

Backbone and side-chain 1H, 13C, and 15N chemical shift assignments for the apo-form of the lytic polysaccharide monooxygenase NcLPMO9C

Abstract: The apo-form of the 23.3 kDa catalytic domain of the AA9 family lytic polysaccharide monooxygenase NcLPMO9C from Neurospora crassa has been isotopically labeled and recombinantly expressed in Pichia pastoris. In this paper, we report the 1 H, 13 C, and 15 N chemical shift assignments of this LPMO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Recent ITC, NMR and docking studies of an AA9 LPMO from Neurospora crassa in contact with oligosaccharides revealed that more extended substrates had significantly higher binding affinities. This is in accord with a multi-point interaction of the substrate with the LPMO surface where the surface loops in some LPMOs remote from the active site enhance binding affinity 21 . The study also showed that a single cellohexaose (Cell 6 ) chain likely spans the copper active site from the −3 to +3 or −2 to +4 subsites (subdivisions of the binding cleft numbered relative to the site of cleavage 32 ), in which the L3 loop (important for interactions with the +3/+4 subsites) and the LC loop (important for binding to approximately −4 subsite) lie at somewhat extended distances from the copper active site.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Recent ITC, NMR and docking studies of an AA9 LPMO from Neurospora crassa in contact with oligosaccharides revealed that more extended substrates had significantly higher binding affinities. This is in accord with a multi-point interaction of the substrate with the LPMO surface where the surface loops in some LPMOs remote from the active site enhance binding affinity 21 . The study also showed that a single cellohexaose (Cell 6 ) chain likely spans the copper active site from the −3 to +3 or −2 to +4 subsites (subdivisions of the binding cleft numbered relative to the site of cleavage 32 ), in which the L3 loop (important for interactions with the +3/+4 subsites) and the LC loop (important for binding to approximately −4 subsite) lie at somewhat extended distances from the copper active site.…”
Section: Introductionsupporting
confidence: 53%
“…We studied substrate binding on both Ls AA9A and Cv AA9A using EPR spectroscopy (Table 3 ) to investigate the electronic state of the active site copper upon binding. As has been shown by Frandsen et al 33 and Courtade et al 21 , the binding affinity of oligosaccharide substrates is significantly affected by the presence of the exogenous ligand on the copper ion. Accordingly, EPR experiments were carried out in both the absence and presence of 200 mM chloride (1.0 M chloride for Xyl 6 studies).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Nevertheless, if suitable reaction conditions, sampling time points and correct calibration data for the detected species are used, HPLC-based methods provide the most accurate results of physiological LPMO activity. NMR has also been used to follow the action of LPMO on polymeric substrates [ 4 , 6 , 11 , 12 ], but its strength lies in the identification of reaction products and not in the measurement of enzymatic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Because LPMO action increases the susceptibility of recalcitrant substrates such as cellulose and chitin to the action of classical glycoside hydrolases (GHs), LPMOs have become an important ingredient in commercial enzyme cocktails for industrial biomass conversion (Hu et al 2014;Müller et al 2015). To create additional insight into LPMO structure and dynamics, and to study substrate binding, several NMR investigations have been conducted (Aachmann et al 2011(Aachmann et al , 2012Courtade et al 2015Courtade et al , 2016aCourtade et al , b, 2017.…”
mentioning
confidence: 99%